ECONOMIES OF POTATO PRODUCTION (BAGHDAD PROVINCE AS A CASE STUDY ) - & AL-Ukeili, AL-Bahadely (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The research aimed at estimating the production function and the total cost function, as well as calculating the efficiency of resource use, technical, economic, price and cost efficiency. The research was based primarily on a simple random sample of 115 farmers in Baghdad governorate for the spring season 2016.The finding of the study reveal that the optimal size of production and the size of production that maximize profit reached about 98.6512, 112.8316 tons respectively. Technical, economic and price efficiencies were estimated at (61.8588, 61.8585, 90.479)% consequently, while cost efficiency was estimated at 0.66720, and the net farm income that achieved over all the sample less about 3726.9726 thousand dinars than that achieved at optimal size. The results of the resources efficiency criteria indicated that potato farmers were efficient in using resources (seeds, human labor) and were inefficient in using the irrigation resource. The research concluded that the quantity of seeds had the greatest impact on potato production and that there was waste in using the available resources, which led to the actual production being less than the optimum size of production. The research recommends that the related institutions should work to provide good quality potato seeds to cover the needs of local farmers, And from good sources in a timely manner and at the right price to increase the production and productivity of this important crop and reduce production costs. As well as the protection of the local producer by adopting price policies that grant best income of farmer.